Factors Affecting Financial Performance in Commercial Banks in Nepal (OCEM Journal of Management, Technology & Social Sciences, 2026)
The financial performance of the banking industry reflects the overall economic status of the banking sector, which is, without doubt, a key part of the Nepalese economy. This study examines the key factors influencing the financial performance of Nepalese commercial banks through a survey-based methodology. A cell-administered questionnaire was employed to gather primary data from a sample of two hundred ten (N = 210) respondents, comprising bank employees, managers, and financial analysts from different commercial banks.The study investigates the strike of  risk management practices, intellectual capital and internal control on financial performance of Nepalese commercial banks using Principal Component Analysis (PCA). The results show that risk management practices, intellectual capital and internal control are statistically significant and influence the financial performance of the Nepalese commercial banks. The results also show how important internal governance and risk management are for improving performance metrics. The study adds to the limited real-world research on Nepal’s banking sector by providing policymakers, regulators, and bankers with useful guidance on how to make the banking sector more stable and profitable.